INDOLE ALKALOIDE, SENYAWA AKTIF PADA CEMPIRIT (ERVATAMIA SPHAEROCARPA) BURCK. - Murningsih, Tri (Research Center for Biology-Indonesian Institute of Sciences, 1998)
Cempirit [Ervatamia svhaerocarva Burck.(Apocynaceae)] is a sticky plant found in Indonesia. This species had long been used as traditional medicine for skin diseases and ulceration of nose.Major biologically active compound was isolated from bark of E.sphaerocarDa by using combination of chromatography techniques (Thin Layer Chromatography,Colum Chromatography and High Performance Liquid Chromatography).The structure of this compound was elucidated by spectroscopic methods, mainly by NMR (Nuclear Magnetic Resonance) spectral. This compound was determined as indole alkaloide called Tabernaemontanine.